The Phenomenology of Micro-Entrepreneurs (MicroTrepreneur Model) in the Philippines (Texas Journal of Multidisciplinary Studies, 2022)
The study aimed in developing an Entrepreneurial Model which is a scenario-based deduced from the operations of Micro-Entrepreneurs in the Philippines which include the factors affecting the profitability (monthly sales, return on investment and tax paid) of the business operations such as Human Capital (access to capital, experience in business, entrepreneurial skills, financial management skills and marketing skills) and Business Strategies (low-cost, differentiation, and focus). It applied the Triangulation (Analysis triangulation of which the same data set is analyzed with the use of two or more differing analyses techniques to cross validate the findings such as descriptive-regression, Interview and Focus group discussion) Method of Research and employed a Cluster Random Sampling technique from the Three Major Geographic Division of the Philippines, the Luzon, Visayas and Mindanao in their Local Government Units (LGUs).